Studi Pemanfaatan Pupuk Organik Cair dari Air Lindi TPA Tlekung Kota Batu dengan menggunakan Ecoenzyme sebagai Biodegradasi Logam Berat (Pb, Cu) - Luluk Indri Astuti; Arie Srihardyastutie; Qonitah Fardiyah (Postgraduate, University of Mataram, 2025)
Leachate is water produced from the waste processing process at the final disposal site (TPA). Leachate contains various organic substances, so many local people use leachate as fertilizer. However, on the other hand, leachate contains heavy metals. As an effort to reduce the content of heavy metals such as Pb and Cu, biological remediation techniques are used by adding ecoenzymes. This study aims to determine the effectiveness of ecoenzymes on leachate at the Tlekung TPA, Batu City. Leachate at the inlet point of Tlekung Landfill, Batu City was taken as much as 20 liters and the volume of ecoenzyme was varied, namely P1 (leachate 1000 ml), P2 (leachate 1000 ml + 1 ml ecoenzyme), P3 (leachate 1000 ml + 5 ml ecoenzyme), P4 (leachate 1000 ml + 10 ml ecoenzyme), P5 (leachate 1000 ml + 15 ml ecoenzyme). The research stages were carried out by testing the pH using a pH meter, testing the number of colonies using the Total Plate Count (TPC) method, testing the levels of lead (Pb) and copper (Cu) using the AAS method. The results showed that the addition of ecoenzyme to leachate affected the pH value, increased the number of colonies and decreased the levels of Pb and Cu metals. The addition of 10 mL of ecoenzyme in 1000 ml of leachate in the P4 treatment could increase the number of colonies and reduce the levels of Pb and Cu.